Composite electrolyte material, preparation method thereof and semiconductor ion fuel cell
Through the doping and cerium oxide-based heterostructure of Li4-2xNi3xTi5-xO12 and CeO2 composite electrolyte materials, the problem of insufficient conductivity and power density of solid oxide fuel cells at low temperatures is solved, and higher battery performance and stability are achieved sex.
Patent Information
- Application Number
- CN202411093001.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-13
AI Technical Summary
The catalytic activity of existing solid oxide fuel cells decreases at low temperatures, resulting in a decrease in ionic conductivity and internal short circuits, affecting battery performance.
Li4-2xNi3xTi5-xO12 and CeO2 composite electrolyte materials are used to dopant Ni and construct a cerium oxide-based heterostructure to improve the ionic conductivity and power density of the battery at low temperatures, suppress electron conductivity, and enhance anti-oxidation performance.
It significantly improves the ion conductivity and power density of solid oxide fuel cells at low temperatures, reduces resistance, enhances the stability and output power of the battery, and avoids internal short circuit.
Smart Images

Figure CN119133541A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid oxide fuel cells, and more specifically, to a composite electrolyte material and a preparation method thereof, and a semiconductor ion fuel cell. Background Art
[0002] Solid Oxide Fuel Cell (SOFC) is a clean and efficient green energy conversion technology. The current main research goal is to reduce the operating temperature. However, when the operating temperature of SOFC is reduced, its catalytic activity will also be greatly reduced, resulting in a decrease in ionic conductivity.
[0003] Semiconductor ion fuel cell (SIFC) is a SOFC that uses a semiconductor and ion conductor composite as the electrolyte. The internal heterogeneous structure of the electrolyte improves the electrochemical performance of the battery at low temperatures (450-600°C) and is considered to be a potential battery for commercialization.
[0004] At present, the commonly used SIFC electrolyte materials are mainly CeO 2 Electrolyte materials, which show excellent electrochemical performance in low temperature regions, but due to CeO 2 In H 2 Under reducing atmosphere, Ce 4+ Easily reduced to Ce 3+ , and accompanied by the generation of electronic conductance, these additional electronic conductances may cause internal short circuits and lead to significant reductions in opening voltage and power.
[0005] Therefore, how to provide a new solid oxide fuel cell electrolyte material so that the battery has excellent conductivity at low temperatures and SIFC has better battery performance is an urgent problem that needs to be solved. Summary of the invention
[0006] In view of this, one of the objects of the present invention is to provide a composite electrolyte material suitable for semiconductor ion fuel cells. The composite electrolyte material provided by the present invention has very excellent performance in low-temperature solid oxide fuel cells (LT-SOFC) and has broad application potential in the commercialization of SOFC.
[0007] To achieve the above object, the technical solution of the present invention is as follows: A composite electrolyte material, the composite electrolyte material is used as an electrolyte for a semiconductor ion fuel cell, the composite electrolyte material is composed of Li 4-2x Ni3x Ti 5-x O 12 and CeO 2 Mix to obtain the Li 4-2x Ni 3x Ti 5-x O 12 and CeO 2 The mixing mass ratio is 6~9:1~4, where 0≤x≤0.1.
[0008] Furthermore, the Li 4-2x Ni 3x Ti 5-x O 12 and CeO 2 The mixing mass ratio is 6~8:2~4.
[0009] Further, 0.05≤x≤0.075.
[0010] In the present invention, cerium oxide-based heterostructure composite materials have become the mainstream trend in the development of SOFC, which require relatively lower operating temperatures and are more stable under reducing conditions. 4+ Reduction to Ce 3+ Electrochemical leakage will occur during the process, and micro cracks will occur due to volume changes, leading to battery operation failure. Batteries using cerium oxide-based heterostructure composite materials as electrolytes can effectively avoid these problems. 4 Ti 5 O 12 , LTO) belongs to the spinel structure, and its lattice structure is composed of lithium ions and titanate ions. LTO has excellent electrochemical properties, which makes it widely used in the battery field. It has the characteristics of high voltage platform, long cycle life and low internal resistance. The most widely used application is as the positive electrode material of lithium battery.
[0011] In the present invention, based on the cerium oxide-based heterostructure composite material and Li 4 Ti 5 O 12 The advantages of LTO are the p-type semiconductor LTO and n-type semiconductor CeO 2 Uniform composite. Constructed LTO-CeO 2 The heterojunction exhibits excellent ionic conductivity and fuel cell performance in the low temperature range (550℃-400℃), suppressing electronic conductivity and promoting ionic conductivity through the pn heterojunction effect, indicating that LTO-CeO 2 Composite materials as SOFC electrolytes are an effective means to improve battery performance.
[0012] Furthermore, the present invention can effectively regulate the performance of the electrolyte and improve the working efficiency and reliability of SOFC by introducing external elements; by reasonably selecting doping elements and doping concentrations, the ionic conductivity can be significantly improved, the resistance can be reduced, and the anti-oxidation performance can be enhanced. 4 Ti 5 O 12 Li has good ion conductivity, and ion doping can further enhance its ion conductivity. This will reduce the internal resistance of the electrolyte and promote the rapid transmission of oxygen ions in the electrolyte, thereby increasing the output power of SOFC. Ion doping can change Li 4 Ti 5 O 12 The lattice structure and defect distribution of the material can be optimized to optimize the ion conduction channel and improve the performance and stability of the material.
[0013] The present invention also aims to provide a solid oxide fuel cell electrolyte material, which is Ni doped Li 4 Ti 5 O 12 , specifically Li 4-2x Ni 3x Ti 5-x O 12 , where 0<x≤0.1.
[0014] Further, 0.05≤x≤0.075.
[0015] In the present invention, only Ni is used to dope Li 4 Ti 5 O 12 , preparation of Li 4-2x Ni 3x Ti 5-x O 12 (0≤ x ≤0.1) electrolyte material, under the condition of 0.05≤x≤0.075, can also significantly improve the power density output and ion conductivity of solid oxide fuel cells at 550℃-400℃.
[0016] The present invention uses Ni doped Li 4 Ti 5 O 12 , preparation of Li 4-2x Ni 3x Ti 5-x O 12 (0≤ x ≤0.1)Electrolyte material and CeO 2 Composite, explore the most suitable doping concentration for LT-SOFC, in the present invention, 0.05≤x≤0.075. 4-2x Ni 3x Ti 5-x O 12 -CeO 2 / Ni-NCAL fuel cell, through electrochemical performance tests and various characterizations, it is proved that Ni doping improves the ionic conductivity and power output of LTO. Appropriate concentration of Ni doping will not change the spinel structure and morphology of LTO, but can provide O 2- and H + The electrolyte material prepared by the present invention exhibits excellent power density output and high ionic conductivity at 550℃-400℃, indicating that Li 4-2x Ni 3x Ti 5-x O 12 (0≤ x ≤0.1) as LT-SOFC electrolyte with CeO 2 Composites are very promising materials.
[0017] The present invention also aims to provide a method for preparing any of the above composite electrolyte materials, comprising the following steps: (1) Preparation of Li 4-2x Ni 3x Ti 5-x O 12 According to Li 4-2x Ni 3x Ti 5-x O 12 The value of x in the equation is, weigh the corresponding amount of Li 2 CO 3 、TiO 2 and NiO powder; Li 2 CO 3 、TiO 2 and NiO powder are placed in a ball mill, anhydrous ethanol is added to mix them, and ball milling is performed; After ball milling, Li is obtained by drying, primary grinding, sintering, and secondary grinding. 4-2x Ni 3x Ti 5-x O 12 powder; (2) According to Li 4-2x Ni 3x Ti 5-x O 12 and CeO 2 The mixed mass ratio is Li 4-2x Ni 3x Ti 5-x O 12 Powder and CeO2 , placed in a ball mill for ball milling, and then dried, ground once, sintered, and ground twice to obtain Li 4-2x Ni 3x Ti 5- x O 12 -CeO 2 Composite electrolyte materials.
[0018] Furthermore, in step (1), an excess amount of the Li 2 CO 3 The amount of , and the excess ratio is 2 to 5%, preferably 3 mol%.
[0019] Furthermore, in step (1), the ball milling speed is 180 r / min, the ball milling time is 6 h, the first grinding and the second grinding time are both 30 min; the sintering time is 6 h, and the sintering temperature is 700-900 °C, preferably 800 °C.
[0020] Furthermore, in step (2), the ball milling speed is 180 r / min, the ball milling time is 6 h; the first grinding and second grinding times are both 30 min; the sintering time is 6 h, and the sintering temperature is 700°C.
[0021] The present invention also aims to provide a semiconductor ion fuel cell containing any of the above-mentioned composite electrolyte materials.
[0022] Furthermore, the electrode material of the semiconductor ion fuel cell is LiNi 0.8 Co 0.15 Al 0.05 O 2 , the LiNi 0.8 Co 0.15 Al 0.05 O 2 Commercially available; LiNi 0.8 Co 0.15 Al 0.05 O 2 After mixing with pinene alcohol, alcohol and PVB, NCAL slurry is obtained, and the NCAL slurry is applied on nickel foam to obtain the electrode of the semiconductor ion fuel cell.
[0023] Compared with the prior art, the present invention has the following advantages: In the present invention, a cerium oxide-based heterostructure composite material and a Li 4 Ti 5 O 12 The advantages of p-type semiconductor Li 4 Ti 5 O 12(LTO) and n-type semiconductor CeO 2 Uniform composite, while further addressing the problems of insufficient ion conductivity and low power density of SOFC in low temperature area, based on solid phase synthesis in Li 4 Ti 5 O 12 (LTO) is doped with metal Ni to obtain Li 4- 2x Ni 3x Ti 5-x O 12 Materials, CeO 2 Compound to obtain Li 4-2x Ni 3x Ti 5-x O 12 -CeO 2 Composite electrolyte materials can significantly improve the ionic conductivity and power density of batteries in the low temperature range (550℃-400℃). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The LTO and CeO prepared in Example 1 of the present invention 2 and composite electrolyte LTO-CeO 2 XRD patterns at different mass ratios.
[0025] Figure 2 (a) LTO, (b) CeO prepared in Example 1 of the present invention 2 and (c) 3LTO-7CeO 2 SEM images of powder and (df) EDS scanning spectra of Ti, Ce, and O elements.
[0026] Figure 3 The single cells prepared with electrolytes of different composite ratios in Example 1 of the present invention at a test temperature of 550°C-400°C are I - V , I - P Output curves, where (a) 1LTO-9CeO 2 (b)2LTO-8CeO 2 、(c)3LTO-7CeO 2 , (d) 4LTO-6CeO 2 .
[0027] Figure 4 The single cells prepared with electrolytes of different composite ratios prepared in Example 1 of the present invention at (a) a test temperature of 550°C I - V , I - POutput curve and (b) pure CeO 2 The single cell prepared by electrolyte at the test temperature of 550℃-400℃ I - V , I - P Output curve.
[0028] Figure 5 This is the ionic conductivity curve of a single cell prepared with electrolytes of different composite ratios prepared in Example 1 of the present invention at 550° C.-400° C.
[0029] Figure 6 The electrolyte material Li prepared in Example 2 of the present invention is 4-2x Ni 3x Ti 5-x O 12 XRD patterns under different sintering temperatures.
[0030] Figure 7 The electrolyte material Li prepared in Example 2 of the present invention is 4-2x Ni 3x Ti 5-x O 12 (a) x =0 (b) x =0.1 SEM picture.
[0031] Figure 8 (a) Li prepared in Example 2 of the present invention 4-2x Ni 3x Ti 5-x O 12 The single cell prepared with electrolyte at 550℃ test temperature I - V , I - P Output curve (b) Li 4 Ti 5 O 12 ( x =0) electrolyte prepared single cell at 550℃-400℃ test temperature I - V , I - P Output curve.
[0032] Fig. 9 The performance test of Li prepared in Example 2 of the present invention is 4-2x Ni 3x Ti 5-x O 12 (0≤ x ≤0.1) cross-sectional SEM images of fuel cells with electrolytes (ab) x=0.025 (cd) x =0.05 (ef) x =0.075 (gh) x =0.1.
[0033] Fig.10 The Li prepared in Example 2 of the present invention and tested at 550°C-400°C 4-2x Ni 3x Ti 5-x O 12 (a) x =0.025(b) x =0.05 (c) x =0.075 (d) x =0.1Electrochemical impedance spectroscopy of fuel cell.
[0034] Fig.11 The electrolyte Li prepared in Example 2 of the present invention 4-2x Ni 3x Ti 5-x O 12 Ionic conductivity curves at 550°C-400°C. DETAILED DESCRIPTION
[0035] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0037] Example 1 1. Preparation of electrolyte materials (x is 0, i.e., undoped Ni) First, according to LTO: CeO 2 =1:9, 2:8, 3:7, 4:6 mass ratio respectively weigh appropriate amount of Li 4 Ti 5 O 12 and CeO 2Put it in a ball mill, add about 100 mL of ethanol, cover the ball mill and put it in the ball mill, set the operating parameters, and ball mill at a speed of 180 rad / min for 6 hours. After the ball milling is completed, use a syringe to take out the evenly mixed liquid in the ball mill, put it in a beaker, and then use a baking lamp to dry the resulting liquid until the ethanol evaporates completely. Put the dried mixed material into a mortar and grind it thoroughly for 30 minutes, then put it into a muffle furnace for sintering at 700°C for 6 hours, and then obtain a uniform Li 4 Ti 5 O 12 -CeO 2 Composite electrolyte powder.
[0038] The powder was subjected to XRD test, and the results were as follows: Figure 1 As shown, the samples of this embodiment, LTO, CeO 2 It is purchased commercially, and the XRD spectra correspond to the corresponding standard diffraction spectra (PDF#49-0207) and (PDF#43-1002). It can be seen from the figure that the XRD diffraction peaks of the composite electrolyte correspond to the diffraction peaks of the single-phase material one by one, and no other impurity peaks appear, and there is no peak shift phenomenon. The composite material has been sintered at 700℃. The XRD spectra of the composite electrolyte materials with four mass ratios have the same phenomenon, and no impurity phase appears. And as the mass ratio of LTO increases, the diffraction peak intensity increases. The XRD spectrum shows that LTO, CeO 2 The two-phase materials have no obvious chemical interaction during solid-phase mixing and sintering, do not produce by-products, and have stable chemical compatibility.
[0039] The powder was analyzed by SEM and EDS. Figure 2 As shown; LTO particles are spherical and evenly distributed, with a particle size between 1-5 μm. 2 It is a cubic crystal with a size between 1-3 μm. Smaller CeO can be seen in the composite material. 2 The particles and larger LTO particles are evenly and continuously distributed. The composite material is obtained by ball milling. After rapid and uniform ball milling, the particle size of the composite material is significantly reduced, which is more conducive to the interface effect between the two phase materials, increases the ion fast transmission channel, improves the battery performance, and achieves higher battery output power. In addition, the uniformity of the two phase materials in the heterogeneous structure is the basic requirement for building a continuous network and charge transfer path. Therefore, in order to further verify the CeO 2 The uniform distribution of LTO phase and 3LTO-7CeO was investigated by EDS. 2 The composite electrolyte material was subjected to elemental analysis. All elements contained in the two-phase material were uniformly distributed in the composite material, indicating that CeO 2The two phases of Li and LTO were mixed evenly to obtain a uniform composite electrolyte material. Due to the test equipment, the Li element could not be detected, but the test results of other elements were sufficient to prove the uniformity of the composite material.
[0040] 2. Prepare NCAL electrodes according to the following method: S201. Prepare nickel foam and use a punch to punch out circles with a diameter of 13 mm on the nickel foam (generally 20 circles are punched, corresponding to 10 g of NCAL) to facilitate coating of slurry and cutting of circular electrodes; S202, according to the material ratio, using an electronic balance to weigh corresponding grams of NCAL powder (commercially available) and PVB powder; S203, putting the weighed two powders into a mortar, taking corresponding amounts of pinene alcohol and anhydrous ethanol with a rubber-tipped dropper according to the material ratio, adding them to the powders, and continuously grinding them to fully mix them to form a slurry material; S204, using a small brush to dip the slurry, and evenly apply it on the circular area of the nickel foam, so that there are no blank holes in the circular area of the nickel foam; S205, placing the coated nickel foam into a drying oven and drying at 120° C. for 24 min; S206, after drying, take out the nickel foam, continue to coat the slurry to make it more uniform, put it into a drying oven after coating, and continue to dry at 120° C. for 24 min; S207, after drying, take out the nickel foam, slightly dilute the remaining NCAL slurry with anhydrous ethanol, continue coating, make the circular area of nickel foam uniform and the surface smooth, put it into a drying oven after coating, and dry it at 120°C for 30 min; S208. After drying, take out the nickel foam and cut it into circular areas to obtain a circular electrode sheet with a diameter of 13 mm, namely, a Ni-NCAL electrode.
[0041] 3. Preparation of batteries With Ni-NCAL as electrode, Li 4 Ti 5 O 12 -CeO 2 As electrolyte, the battery Ni-NCAL / Li 4 Ti 5 O 12 -CeO 2 / NCAL-Ni; Preparation of battery Ni-NCAL / Li 4 Ti 5 O 12 -CeO 2 / NCAL-Ni includes the following steps: S301. Use an electronic balance to weigh 0.3-0.32 g of Li 4 Ti 5 O 12 -CeO 2 Electrolyte powder, weigh and set aside; S302, wiping the battery mold to ensure that all parts of the mold are clean and free of impurities; S303, after wiping is completed, take out the two gaskets in the abrasive tool, and put one of the gaskets into the abrasive tool with the smooth side facing upward; S304, take two electrode sheets, put one electrode sheet with the convex surface facing upward into a battery mold, and flatten it; S305, pour the weighed electrolyte powder evenly into the mold, and press the powder flat; S306, placing another electrode sheet with the raised surface facing downward into the mold, and gently pressing to form a three-layer structure of electrode sheet / electrolyte / electrode sheet, and placing another gasket into the mold with the smooth surface facing downward; S307, placing the entire mold on a tablet press and pressing at 400 MPa for 80 s; S308. After the pressing is completed, take out the battery from the mold to obtain Ni-NCAL / xLTO-yCeO 2 / Ni-NCAL single cell.
[0042] 4. Performance Testing The Ni-NCAL electrode prepared in the above steps was used as the cathode and anode, and the xLTO-yCeO 2 Preparation of single cell Ni-NCAL / xLTO-yCeO as electrolyte 2 / Ni-NCAL, tested in the low temperature range of 550-400℃, the IV (current-voltage) and IP (current-power density) characteristics of the device are as follows Figure 3 As shown; Using 1LTO-9CeO 2 、2LTO-8CeO 2 、3LTO-7CeO 2 、4LTO-6CeO 2 The maximum power density (MPD) of the fuel cell battery with the material as the electrolyte at 550°C is 895 mW·cm -2 、975 mW·cm -2 、1112 mW·cm -2 、925 mW·cm -2 , when LTO and CeO 2The battery showed the best power output when the composite ratio was 3:7. This may be because the heterojunction interface effect provided the most ion transport channels at this ratio, which improved the ion conductivity and thus improved the electrochemical performance of the battery.
[0043] Figure 4 The IV and IP output curves of the single cells prepared with different composite ratio electrolytes prepared in this embodiment at a test temperature of 550°C and the pure CeO 2 IV and IP output curves of single cells prepared with electrolyte at test temperatures of 550℃-400℃.
[0044] pass Figure 4 It can be seen that as the mass ratio of LTO increases from 0 to 40%, the MPD of the battery gradually increases and then decreases, and the open circuit voltage (OCV) continues to increase, indicating that the introduction of LTO in the electrolyte layer can increase the open circuit voltage of the battery. LTO can effectively solve the problem of CeO 2 Center 4+ Reduction to Ce 3+ The more electronic conductivity brought by the battery can avoid short circuit. The battery power density test results show that 3LTO-7CeO 2 The pn heterojunction formed by the heterostructure composite electrolyte can more effectively block the transmission of electrons and promote the transmission of ions.
[0045] Figure 5 The LTO-CeO prepared in this example 2 Ionic conductivity test results of the electrolyte material of the composite electrolyte fuel cell after electrochemical testing.
[0046] The ionic conductivity of a battery can be measured by I - V The characteristic curve is obtained, I - V The straight line part of the characteristic curve reflects the ohmic polarization process of the battery, which is caused by the electrolyte resistance, that is, the ionic resistance. I - V The slope of the straight line portion of the curve is calculated, so the ionic conductivity can be calculated according to the following formula:
[0047] in, L represents the thickness of the electrolyte, R represents the ionic resistance, S Represents the active area of the battery.
[0048] This example calculates the ionic conductivity of all electrolyte ratios. Since temperature has the greatest impact on ion migration, the ionic conductivity decreases as the temperature decreases. At the lowest temperature of 400°C, the ionic conductivity of the five electrolytes is very small. This is mainly due to the temperature limiting the ionic conductivity. As the LTO mass ratio increases, the ionic conductivity increases first and then decreases. 2 The ionic conductivity is the highest in the electrolyte, which verifies the previous speculation of the present invention that the improvement of battery performance comes from the increase of ionic conductivity. 2 The material is a promising electrolyte in SOFC.
[0049] Example 2 1. Synthesis of Li 4-2x Ni 3x Ti 5-x O 12 powder S101. Prepare medicines 2 CO 3 、TiO 2 , NiO, according to the doping concentration ( x =0, 0.025, 0.05, 0.075, 0.1) Calculate the mass of the required medicine and weigh the corresponding grams of Li using an electronic balance 2 CO 3 、TiO 2 and NiO powder. To compensate for the loss of lithium during high-temperature sintering, an excess of 3 mol% lithium carbonate was used; S102, weigh the Li 2 CO 3 、TiO 2 Put the NiO powder into a ball mill, add anhydrous ethanol to mix, cover the ball mill and put it into a ball mill, set the ball mill operating parameters, the speed is 180 r / min, and the operating time is 6 h; S103, after the ball milling is completed, the mixed liquid in the ball milling tank is taken out with a syringe, put into a beaker, and dried with a baking lamp; S104, taking out the dried mixed material, putting it into a mortar and grinding it for 30 minutes to obtain a powder material; S105. Place the material in a muffle furnace and sinter it at different temperatures for 6 h to explore the phase formation temperature of the material; S106, after sintering, was ground in a mortar for 30 min to obtain Li 4-2x Ni 3x Ti 5-x O 12 powder.
[0050] The powder was subjected to XRD test, and the results were as follows: Figure 6 As shown, the prepared electrolyte material was sintered at 700°C, 800°C, and 900°C. Figure 6 (ae) are five doping concentrations of Li 4-2x Ni 3x Ti 5-x O 12 XRD test of the material after sintering at different temperatures. As can be seen from the figure, as the sintering temperature increases, the diffraction peak intensity of the material gradually increases, indicating that the crystallinity of the crystal is improving. At 700℃, there are a lot of impurity peaks. After comparing with the standard card, most of the impurity peaks are TiO 2 The diffraction peaks of the original material are not fully reacted at 700°C and the temperature required for the reaction to be completed is not reached. The impurity peaks disappear at 800°C, and the diffraction peaks correspond to the standard card PDF#49-0207, indicating that the present invention obtains pure Li 4-2x Ni 3x Ti 5-x O 12 When sintered at 900℃, the material also forms a phase. Compared with the diffraction peak obtained by sintering at 800℃, the diffraction peak intensity is slightly lower, so 800℃ is Li 4-2x Ni 3x Ti 5-x O 12 The optimum phase formation temperature of the material. Figure 6 (f) is Li 4-2x Ni 3x Ti 5-x O 12 (0≤ x ≤0.1) In the XRD spectrum after sintering at 800℃, there are no impurity peaks, and all peaks in the figure can be indexed as having The sharp peaks indicate that all samples have good crystallinity, indicating that Ni ions have successfully entered the Li 4 Ti 5 O 12 in the crystal lattice.
[0051] The powder was subjected to SEM analysis, and the results were as follows: Figure 7 As shown; The microstructure of the material was observed by SEM. 4-2x Ni 3x Ti 5-x O 12 (0≤ x ≤0.1) The powders obtained after sintering at 800℃ for 6 h have similar morphology. After Ni doping, the morphology of the samples has almost no change. Figure 7 Shown x =0 and x=0.1 SEM images of two samples, one is a sample without Ni doping, and the other is a sample with the highest Ni doping amount. It can be seen from the figure that the material size and particle shape after Ni doping have not changed, and the particle size is about 500 nm. The material prepared by high-temperature solid phase method has a small particle size and uniform distribution. Nanoscale materials have the advantages of high surface area and high surface reaction energy, which can greatly improve material properties.
[0052] 2. Preparation of NCAL Electrode S201, first use a punch to cut Foam-Ni into discs with a diameter of 13 mm, 10 g NCAL slurry corresponds to 20 Foam-Ni discs; S202, mixing NCAL powder, pinene alcohol and PVB in a certain proportion, and adding an appropriate amount of anhydrous ethanol to form a slurry for standby use; S203, coating the prepared electrode slurry evenly on Foam-Ni until the entire circular part has no holes or light is transparent and drying in a drying oven at 120° C. for 24 min; S204, after taking out the coated electrode, pour a little anhydrous ethanol into the remaining NCAL slurry to further dilute it, and apply it on the electrode, and continue to dry at 120°C / 24 min; S205. Finally, the used NCAL slurry is diluted again with anhydrous ethanol, the surface of the circular NCAL electrode is smoothed and exposed to metallic luster, and dried at 120° C. for 30 min to obtain a Foam-Ni-NCAL electrode sheet.
[0053] 3. Preparation of batteries S301. Use an electronic balance to weigh an appropriate amount of Li 4-2x Ni 3x Ti 5-x O 12 Electrolyte powder, weigh and set aside; S302, clean the battery preparation mold and place a coated Foam-Ni-NCAL electrode (NCAL surface contacts Li 4-2x Ni 3x Ti 5-x O 12 Electrolyte), Li 4-2x Ni 3x Ti 5-x O 12 The electrolyte material is poured evenly and slowly on the Foam-Ni-NCAL electrode; S303, using the battery preparation mold to 4-2x Ni 3x Ti 5-x O 12The electrolyte is flattened and no pores appear; S304, place another Foam-Ni-NCAL electrode on the flat Li 4-2x Ni 3x Ti 5-x O 12 Powder (NCAL surface contact Li 4-2x Ni 3x Ti 5-x O 12 electrolytes); S305. Finally, the battery preparation mold is placed in a tablet press, and the symmetrical electrodes and electrolyte in the battery preparation mold are pressed into a three-layer battery at a pressure of 400 MPa. The effective electrode area of the battery is 0.64 cm 2 , diameter is 13mm; S306, placing circular nickel foam of equal size on both sides of the battery prepared above, and clamping it in a battery test fixture to obtain Ni-NCAL / Li 4-2x Ni 3x Ti 5-x O 12 / Ni-NCAL single cell.
[0054] 4. Performance Testing The battery prepared above was subjected to performance testing.
[0055] Figure 8 This example prepares (a) Li 4-2x Ni 3x Ti 5-x O 12 The single cell prepared with electrolyte at 550℃ test temperature I - V , I - P Output curve, (b) LTO( x =0) electrolyte prepared single cell at 550℃-400℃ test temperature I - V , I - P Output curve.
[0056] Research 4-2x Ni 3x Ti 5-x O 12 Electrochemical performance of electrolyte fuel cells, exploring the optimal Ni doping content, using Ni-NCAL as cathode and anode, and Li 4-2x Ni 3x Ti 5-x O 12Preparation of single cell Ni-NCAL / Li as electrolyte 4-2x Ni 3x Ti 5-x O 12 / Ni-NCAL, tested at a low temperature of 550℃. As can be seen from the figure, the MPD of each battery decreases as the test temperature decreases. Temperature has a great influence on the migration of ions in the battery, which in turn affects the output performance of the battery. In addition, the OCV of all batteries is greater than 1, indicating that the battery has no short circuit problem. As can be seen from the figure, at 550℃, x The MPDs of the cells with the values of =0, 0.025, 0.05, 0.075, and 0.1 are 864 mW·cm -2 , 939 mW·cm -2 , 1078 mW·cm -2 , 1189mW·cm -2 , 975 mW·cm -2 , with the increase of Ni doping content, the maximum power density of the battery first increases and then decreases. x =0.075, the battery power output density is the highest, reaching 1189 mW cm -2 The output performance of LT-SOFC was improved by ion doping, and the performance was improved by about 38%, proving that Li 4 Ti 5 O 12 It is a material with great potential, and Ni performs well as a dopant in LT-SOFC.
[0057] Fig. 9 The performance test of the present invention is Li 4-2x Ni 3x Ti 5-x O 12 (0≤ x ≤0.1) cross-sectional SEM images of fuel cells with electrolytes (ab) x =0.025, (cd) x =0.05 (ef) 、 x =0.075, (gh) x =0.1.
[0058] The morphology of the battery after testing was obtained by SEM, such as Fig. 9This is a cross-sectional view of a battery with a Ni-doped electrolyte after testing. The battery structure is clearly visible in the figure. It has a complete three-layer structure, the electrolyte thickness is relatively uniform, the electrode layers at both ends are relatively loose, and can provide good pores for gas transmission. The electrolyte layer is relatively dense, without cracks and holes, and can isolate the gas. The good contact between the electrode and the electrolyte indicates that the thermal expansion coefficients of the electrode and electrolyte materials match. Good contact between the electrode and the electrolyte can ensure the effective length of the TPB, which is beneficial to increase the reaction active sites, promote the transmission and reaction of gases, ions and electrons, thereby improving the performance and efficiency of the battery and reducing polarization losses.
[0059] Fig.10 The Li prepared by the present invention and tested at 550℃-400℃ 4-2x Ni 3x Ti 5-x O 12 (a) x =0.025 (b) x =0.05(c) x =0.075 (d) x =0.1Electrochemical impedance spectroscopy of fuel cell.
[0060] In air / H 2 Under the conditions, the electrolyte material is Li 4-2x Ni 3x Ti 5-x O 12 (0≤ x ≤0.1) were used for electrochemical impedance spectroscopy test, and the data after the test were fitted using ZSimpWin software. 0 (R 1 Q 1 )(R 2 Q 2 ) equivalent circuit model is used for simulation. As the Ni doping content increases, R 0 First decrease and then increase. x =0.075, R 0 The smallest, indicating that the electrolyte material has the best performance. Ni doping improves the interface properties between the electrode and the electrolyte, reduces the interface resistance, facilitates the rapid transmission of electrons and ions, and reduces the internal impedance of the battery. In addition to optimizing the interface properties, Ni doping can promote the migration rate of ions in the electrolyte, so that the ohmic impedance of the battery becomes smaller. The main function of Ni doping is to improve battery performance by increasing ionic conductivity.
[0061] Fig.11 The electrolyte Li prepared in this example 4-2x Ni 3x Ti 5-x O 12Ionic conductivity curves at 550°C-400°C.
[0062] The ionic conductivity of a battery can be measured by I - V The characteristic curve is obtained, and the ionic resistance is obtained by I - V The slope of the straight line portion of the curve is calculated, so the ionic conductivity can be calculated according to the following formula:
[0063] in, L represents the thickness of the electrolyte, R represents the ionic resistance, S Represents the active area of the battery.
[0064] It can be seen from the figure that as the temperature decreases, the ionic conductivity decreases significantly, and temperature plays an important role in the movement of ions. As the Ni doping content increases, the ionic conductivity first increases and then decreases. x =0.075, the ionic conductivity is the largest, which also proves that the reduction of battery ohmic impedance is due to the increase of ionic conductivity, and x =0.075 when the electrolyte performance is the best. At 550℃ electrolyte Li 4-2x Ni 3x Ti 5-x O 12 ( x =0.075) reaches 0.1533 S·cm -1 , which is about 1.4 times that of undoped Ni. This verifies the previous speculation of the present invention that the improvement of battery performance comes from the increase in ionic conductivity. 4-2x Ni 3x Ti 5-x O 12 The material is a promising electrolyte in SOFC.
[0065] Example 3 In this example, the Li prepared in Example 2 4-2x Ni 3x Ti 5-x O 12 The materials were compounded according to the method in Example 1 to obtain 3Li 4-2x Ni 3x Ti 5-x O 12 -7CeO 2 Composite electrolyte, where x=0.075.
[0066] The battery Ni-NCAL / 3Li was prepared in the same manner as in Example 1. 4-2x Ni3x Ti 5-x O 12 -7CeO 2 / NCAL-Ni.
[0067] After testing, the maximum power density of the battery prepared in this embodiment is further improved in the low temperature range of 550°C, which shows that in the present invention, the LTO doped with Ni and CeO 2 The composite electrolyte can further improve the performance of SOFC.
[0068] Comparative Example 1 In this embodiment, compared with embodiment 1, the difference is that LTO is replaced by La 1−2x Ba x Bi x FeO 3 .
[0069] In this embodiment, it is used as the electrolyte of the low-temperature solid oxide fuel cell and combined with CeO 2 Composite, after testing, the best composite composition is 90CeO 2 -10La 1−2x Ba x Bi x FeO 3 .
[0070] Optimal composition 90CeO 2 -10La 1−2x Ba x Bi x FeO 3 The peak power density of electrolyte-based SOFC at 550°C is 834 mW·cm -2 , the open circuit voltage (OCV) is 1.04 V, which is much smaller than the peak power density at the optimal composite ratio in Example 1 of the present invention.
[0071] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A composite electrolyte material, characterized in that: The composite electrolyte material is used as an electrolyte for a semiconductor ion fuel cell. The composite electrolyte material is composed of Li 4-2x Ni 3x Ti 5-x O 12 and CeO2, the Li 4-2x Ni 3x Ti 5-x O 12 The mixing mass ratio of CeO2 is 6~9:1~4, where 0≤x≤0.
1.
2. The composite electrolyte material according to claim 1, characterized in that The Li 4-2x Ni 3x Ti 5-x O 12 The mass ratio of mixing with CeO2 is 6~8:2~4.
3. The composite electrolyte material according to claim 1, characterized in that 0.05≤x≤0.075。 4. The method for preparing the composite electrolyte material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Preparation of Li 4-2x Ni 3x Ti 5-x O 12 According to Li 4-2x Ni 3x Ti 5-x O 12 For the value of x, weigh the corresponding amount of Li2CO3, TiO2 and NiO powder; Li2CO3, TiO2 and NiO powders are placed in a ball mill, anhydrous ethanol is added to mix them, and ball milling is performed; After ball milling, Li is obtained by drying, primary grinding, sintering, and secondary grinding. 4-2x Ni 3x Ti 5-x O 12 powder; (2) According to Li 4-2x Ni 3x Ti 5-x O 12 The mixed mass ratio of Li and CeO2 is 4-2x Ni 3x Ti 5-x O 12 The powder and CeO2 are placed in a ball mill for ball milling, and then dried, ground once, sintered, and ground twice to obtain Li 4-2x Ni 3x Ti 5-x O 12 -CeO2 composite electrolyte material.
5. The preparation method according to claim 4, characterized in that: In step (1), the amount of Li2CO3 is weighed in excess, and the excess ratio is 2-5%.
6. The preparation method according to claim 4, characterized in that: In step (1), the ball milling speed is 180 r / min, the ball milling time is 6 h, the first grinding and the second grinding time are both 30 min; the sintering time is 6 h, and the sintering temperature is 700~900°C.
7. The preparation method according to claim 4, characterized in that: In step (2), the ball milling speed is 180 r / min, the ball milling time is 6 h; the first grinding and second grinding times are both 30 min; the sintering time is 6 h, and the sintering temperature is 700 °C.
8. A semiconductor ion fuel cell comprising the composite electrolyte material according to any one of claims 1 to 3.
9. The semiconductor ion fuel cell according to claim 8, characterized in that: The electrode material of the semiconductor ion fuel cell is LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.8 Co 0.15 Al 0.05 O2 is mixed with pinene alcohol, alcohol and PVB to obtain NCAL slurry, which is then applied to nickel foam to obtain the electrode of the semiconductor ion fuel cell.
